Operational Optimization for Microgrid of Buildings with Distributed Solar Power and Battery - Zhang, Yuanming; Jia, Qing‐Shan (Asian journal of control, 2017)
Improving building energy efficiency is significant for energy conservation and environmental protection. When there are multiple buildings with solar power generation and batteries connected in a microgrid, coordinating the distributed energy supply and consumption may substantially improve the energy efficiency. We consider this important problem in this paper and make the following three major contributions. First, we formulate the operation optimization of a microgrid of buildings as a two‐stage stochastic programming problem. Second, the problem is transformed into a stochastic mixed‐integer linear programming. Then the scenario method is used to solve the problem. Third, case studies of a university campus is presented. The numerical results show that coordinating the distributed solar power and battery can reduce the operational cost of the microgrid.